Penerapan Kompres Hangat dalam Menurunkan Demam pada Pasien Kejang Demam - Sudariyekti, Arian Wirani; Irdawati, Irdawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effectiveness of applying warm compresses to reduce hyperthermia in children experiencing febrile seizures. This study method uses a case study method with a nursing process. The results of this study through the dependent T-test analysis, namely the P-Value, is 0.000, which is smaller than the significant level α (0.05). In conclusion, giving warm compresses to patients with febrile seizures has significantly reduced children's fever. Keywords: Hyperthermia, Febrile seizures, Warm compresses